2010
DOI: 10.1038/sj.bjc.6605646
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internet peer-support groups on psychosocial adjustment to cancer: a randomised study

Abstract: BACKGROUND: We conducted a randomised study to investigate whether providing a self-guided Internet support group to cancer patients affected mood disturbance and adjustment to cancer. METHODS: Baseline and 1-, 6-and 12-month assessments were conducted from 2004 to 2006 at a national rehabilitation centre in Denmark. A total of 58 rehabilitation course weeks including 921 survivors of various cancers were randomly assigned to a control or an intervention group by cluster randomisation. The intervention was a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
111
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 19 publications
3
111
3
1
Order By: Relevance
“…No difference between the intervention and control groups was found for most measures of mood and adjustment to cancer at any of the three time points. However, the intervention group demonstrated less reduction in helplessness, and increased anxious preoccupation, confusion and depression at 6 months compared with controls [42]. -12).…”
Section: Interventions Connecting Patients With Each Othermentioning
confidence: 74%
See 1 more Smart Citation
“…No difference between the intervention and control groups was found for most measures of mood and adjustment to cancer at any of the three time points. However, the intervention group demonstrated less reduction in helplessness, and increased anxious preoccupation, confusion and depression at 6 months compared with controls [42]. -12).…”
Section: Interventions Connecting Patients With Each Othermentioning
confidence: 74%
“…This review includes studies of patients with lung cancer [31], prostate cancer [32], head and neck cancer [33] and breast cancer [34][35][36][37][38][39][40], as well as mixed cancer populations [41][42][43][44].…”
Section: Cancer Populationmentioning
confidence: 99%
“…It is already known that patients can be valuable sources of expertise for other patients in similar situations, 36 and for this reason, patient representatives will participate as patient experts in the online discussion forums. Results from previous studies have shown that an online discussion forum, moderated by health professionals, can lead to a reduction in mental disorders, whereas an unmoderated forum can, at worst, lead to an increase.…”
Section: Internet-based Learning and Self-care Programmentioning
confidence: 99%
“…Research examining online peer support has primarily focused on the benefit of this support alone, not in combination with a structured psychological intervention. Unfortunately, results have been inconsistent [27,[29][30][31][32]. The current study allowed an analysis of each component of the intervention separately.…”
Section: Discussionmentioning
confidence: 95%